Delta Opioid Receptor Pharmacology and Therapeutic Applications (Handbook of Experimental Pharmacology,, 2018)
This volume describes our current understanding of the biological role of the delta-opioid receptor (DOR) system, focusing on its unique mechanisms of receptor trafficking and signaling in disease states. Part 1 covers the endogenous ligands that regulate the DOR system as well as novel compounds and therapies used to modulate the DOR system. Part 2 describes new insights into the localization and trafficking of the DOR and how ligand-directed signaling alters the fate of the receptor. Part 3 concentrates on the potential role of the DOR system in disease states, such as pain, mood, addiction, and Parkinson's disease. Throughout the book, the DOR system as a target for drug development will be discussed.